Քաղաքական երկխոսությունը քաղաքացիական մշակույթի համակարգում - Սարոյան, Կնյազ (YSU Journal of International Affairs, 2017)
In the article, on the bases of analysis of the Armenian domestic political events, it is demonstrated that one of the main peculiarities of Armenian political life is believed to be tense, conflicting relations. It is expressed in the communication levels between authority and opposition and on the other hand, between authority and the society. Based on the analysis of the public relations’ modern two-sided symmetric dialogical concepts, the article suggests using political dialog as an effective tool for the improvement of the situation. Considering the political dialogue as an element of sustainable civic culture, the article argues that the use of dialogical practices can have a positive impact on the further democratization process of the Republic of Armenia.
Keywords: civic culture, political dialog, political discourse, dialogical turn